(untitled) (Andamios, Revista de Investigación Social, 2010)
Since 1919, the Mexican Government subscribes and ratifies international trades. However, there are not empirical studies that reveal neither their level of efficiency nor the State actions taken afterwards. In that sense, this work tries to response the next question: Do international trades have some utility in Mexico? Given that the universe of population is too extensive, the analysis is limited to a concrete case: the women labor discrimination in the occupational market. For that, it is built and analyzed in an exploratory way, a set of variables that could serve on the future for building an index of efficiency which measures empirically the impact of the sign of those agreements and trades and their compliance by the Mexican State.